Global development finance : financing the poorest countries 2002 (Washington, DC, 2002)
The Global Development Finance (GDF) 2002 examines the current global economic slowdown, and the prospects for global economic recovery. Due to increased global integration, the prospects for developing countries are now more closely tied to trends in global growth and trade patterns. Key themes that emerge from this report stress that further progress in poverty reduction will require improvements in the investment climate in developing countries, an increase in the financial assistance from industrial countries, and an opening of industrial country markets